Avaliação do impacto da fragmentação de florestas nativas sobre a mesofauna edáfica na região de Dourados-MS - Gomes, Ana Amélia (2007)
This work aimed to evaluate the impact of fragmentation on populational dynamic of individual of soil mesofauna in three fragments of native forests in Dourados-MS, from which two of them are located inside indigenous area (Jaguapiru and Bororó) and the third in a non-indigenous area (Azulão farm). For evaluating the impact of fragmentation, number of Oribatid and Gamasida Acari and Collembola insects in these three areas of study was evaluated using a modified Berlesse funnel. It was observed that Bororó fragment presented a total average number of 8.42 organisms, Jaguapiru with 11.25 and Azulão with 16.74. Oribatida and Gamasida Acari were the most numerous organisms in both three studied areas.